When nurses can draw the line in the O.R. - Rozovsky, Lorne; Rozovsky, Fay (Operating Room Nurses Association of Canada Journal, 1988)
The nurse may dislike working with the surgeon who has a reputation of being verbally abusive of staff in the O.R. The nurse has been on the receiving end of the surgeon's childish but violent tantrums. The nurse has heard that the physician threw a used syringe across the O.R. last week because the nurse assisting him was not “quick enough.” Several staff nurses have reported feeling “ill” after their last several shifts in a particular operating room. Some O.R. nurses feel that they are not qualified to assist in a particularly delicate operation. A few O.R. nurses strongly disagree with their supervisor over scheduling on the basis that staff are stretched to the limit. They are tired and bound to “make mistakes," jeopardizing patient care and safety.